2019
DOI: 10.1080/24750573.2019.1619258
|View full text |Cite
|
Sign up to set email alerts
|

Processing speed may improve earlier than response inhibition/ interferens in children with ADHD-combined type receiving methylphenidate: a single-center study

Abstract: OBJECTIVES: The aim of this study was to determine the order of improvement in response inhibition, interference capacity, and processing speed in the Stroop test after starting methylphenidate treatment in children with ADHD. METHODS: This study included a total of 52 children aged 7-16 years who were diagnosed with combined-type ADHD for the first time and who began to use methylphenidate treatment. The Stroop test was applied to each subject at least 3 times (before treatment and at the first and second mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Studies have reported that executive dysfunction is present in both ADHD and obesity (Çetin et al, 2019; Cserjési et al, 2007). In addition, the short-term memory capacity of children diagnosed with ADHD is reported to be lower than that of healthy controls (Kılıç et al, 2007).…”
mentioning
confidence: 99%
“…Studies have reported that executive dysfunction is present in both ADHD and obesity (Çetin et al, 2019; Cserjési et al, 2007). In addition, the short-term memory capacity of children diagnosed with ADHD is reported to be lower than that of healthy controls (Kılıç et al, 2007).…”
mentioning
confidence: 99%